Electroacupuncture for poststroke spasticity (EAPSS): protocol for a randomised controlled trial. Issue 2 (27th February 2018) - Cai, Yiyi; Zhang, Claire Shuiqing; Ouyang, Wenwei; Li, Jianmin; Nong, Wenheng; Zhang, Anthony Lin; Xue, Charlie Changli; Wen, Zehuai
Abstract : Introduction: Spasticity is a common complication of stroke. Current therapies for poststroke spasticity (PSS) have been reported to be associated with high costs, lack of long-term benefit and unwanted adverse events (AEs). Electroacupuncture (EA) has been used for PSS, however, its efficacy and safety is yet to be confirmed by high-quality clinical studies. This study is designed to evaluate the add-on effects and safety profile of EA when used in combination with usual care (UC). Methods and analysis: This study is a parallel group randomised controlled trial. A total of 136 participants will be included and randomly assigned to either the treatment group (EA plus UC) or the control group (UC alone). Prior to the main trial, a pilot study involving 30 participants will be conducted to assess the feasibility of the trial protocol. EA will be administered by registered acupuncturists for 20min to 30 min, three times per week for 4 weeks. The primary outcome measure (Modified Ashworth Scale) and secondary outcome measures (Fugl-Meyer Assessment and Barthel Index) will be evaluated at baseline, the end of treatment (week 4) and the end of follow-up (week 8). AEs will be monitored, recorded and reported, and their causality will be explored. Ethics and dissemination: Ethics approval was obtained from the ethics committees of Guangdong Provincial Hospital of Chinese Medicine and RMIT University in December 2016. The results will be disseminated in a peer-reviewed journal, and PhD theses and might be presented at international conferences. Trial registration number: ChiCTR-IOR-16010283; Pre-results.